Evolution of flow characteristics through finite-sized wind farms and influence of turbine arrangement. (January 2018) - Sharma, V.; Cortina, G.; Margairaz, F.; Parlange, M.B.; Calaf, M.
Abstract: Evolution of flow characteristics through finite-sized wind farms and the influence of the wind-farm configuration on modulating this evolution is explored through numerical simulations. The principal aim for the study is to identify regions of flow-adjustment and flow equilibrium within the wind farm. Towards this aim, a suite of five large-eddy simulations (LES) of the neutral atmospheric boundary layer with extremely long streamwise domains are performed with embedded finite-sized wind farms of different streamwise and spanwise spacing. Three diagnostic variables, namely, the wind-farm induced effective surface roughness, the wake viscosity and the wake-expansion coefficient are computed using the LES-generated database and are used to characterize the flow. Computation of the diagnostic variables is relevant to the wind-energy community in different contexts ranging from parametrization of wind farms in weather and climate models, to wind-farm design and optimization based on wake-models and eddy-viscosity type Reynolds-averaged Navier-Stokes solvers. Results show that flow equilibrium is achieved in the 'most dense' configuration of s x ≈ 8 D, s y ≈ 5 D at approximately the 19 th row. Results also indicate that the streamwise spacing plays a dominant role determining the rate at which flow-adjustment is achieved within the wind farm. Highlights: LES of finite-sized wind-farms embedded in neutral ABL have been performed. Downstream evolution of effective roughness and wake viscosity is highlighted. Regions of flow-adjustment and flow-equilibrium are identified for each case. Row-wise wake-expansion coefficients are computed using an optimization procedure. Influence of turbine arrangement on flow-adjustment and equilibrium is explained.